Power quality enhancement by using Z-DVR based series voltage compensation with black widow optimization technique - Ch. Srivardhan Kumar; Z. Mary Livinsa (Institute of Advanced Engineering and Science, 2023)
In distribution system, voltage quality issues are the most concerning disturbances influencing the power quality (PQ). As a result, to alleviate this PQ concerns such as sag, swell, fluctuation, interruption, and harmonics on the sensitive load, the series voltage compensator dynamic voltage restorer (DVR) is utilized. Furthermore, a Z-source inverter (ZSI) based DVR is proposed in this paper to improve the power system's voltage restoration properties. To compensate the voltage concerns which is occurs in passive and transmission components, the 3-φ Z-DVR inverter with proportional integral derivative (PID) controller tuned by black widow optimization (BWO). By short circuiting the legs of inverter in the ZSI, prepare the possibility of buck and boost in voltage and utilize the LC impedance grid which incorporated power source to inverter circuit. In addition, to obtain the injecting voltage, PID control scheme for ZSI based DVR is proposed in this paper. The proposed modelling and simulation of DVR is implemented in MATLAB/Simulink tool and the outcomes are analyzed. Furthermore, reduction in voltage concerns, and total harmonics distribution (THD) with BWO tuned PID controller is superior which is 1.01% when compared with existing methods such as Harris Hawks optimization (HHO) based PID, genetic algorithm (GA) based PID controller.